Case Report: Gait training using a wearable ankle-exoskeleton in a pediatric patient with Guillain–Barré syndrome - David Cordero-Cuevas; Jimena Figueroa-Valero; Elizabeth Pérez-Rodríguez; Raide Alfonso González-Carbonell (Frontiers in Pediatrics, 2026)
Introduction Guillain–Barré syndrome (GBS) is an acute inflammatory demyelinating polyradiculoneuropathy that can lead to severe gait impairment and functional limitations in pediatric patients. Although conventional physiotherapy (CT) is the standard of care, recovery is often prolonged and characterized by persistent deficits in strength and motor control. Wearable ankle-exoskeletons have emerged as a potential adjunctive tool for task-specific gait training; however, their application in pediatric GBS remains largely unexplored. The aim of this single case report was to describe the clinical application of a structured gait training program using the Biomotum SPARK® wearable ankle-exoskeleton (SPARK®) combined with CT in a pediatric patient with GBS. Results Discrete variations in muscle strength, spatiotemporal parameters, pelvic kinematics, and muscle activation patterns were recorded between baseline (T0) and post-intervention (T2) assessments. Clinically, manual muscle testing scores suggested localized gains, particularly in bilateral hip abductors (moving from 3/5 to 4/5). Instrumented gait analysis indicated a baseline cadence variation from 101.7 to 108.5 steps/min, alongside a displacement of the gait symmetry index from 1.17% to 0.67%. Pelvic kinematic profiles suggested a trend toward alignment with normative reference bands, notably in pelvic obliquity and right pelvic rotation. Furthermore, surface electromyography recordings suggested localized modifications at T2, characterized by a lower envelope amplitude in the right gastrocnemius medialis activation pattern during the swing-phase (60%–100%) and an increase in amplitude within the normative activation periods of the left tibialis anterior. Conclusions This single case report describes the clinical application of an integrated gait training protocol using the SPARK®, which was well-tolerated by the pediatric patient during the recovery-phase of GBS. However, these preliminary observations cannot be generalized or attributed solely to the wearable ankle-exoskeleton, as they likely reflect the combined, synergistic influence of spontaneous neurological recovery, conventional rehabilitation, motor learning, and increased walking exposure. Further controlled studies are necessary to evaluate the potential role and efficacy of wearable ankle-exoskeletons in pediatric GBS rehabilitation.